2018
DOI: 10.1016/j.jamcollsurg.2017.12.027
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter Randomized Trial to Evaluate Hematologic Toxicities after Hyperthermic Intraperitoneal Chemotherapy with Oxaliplatin or Mitomycin in Patients with Appendiceal Tumors

Abstract: Background Appendiceal cancer is a rare disease, which has proven difficult to study in prospective trials. Cytoreductive surgery with HIPEC is an established therapy for peritoneal dissemination from appendiceal cancer. The optimal chemotherapeutic agent to use in the HIPEC is not clear. Mitomycin has long been the utilized, however our previous phase I experience, and European retrospective studies suggest oxaliplatin as an alternative. Therefore, we initiated a multicenter randomized trial to compare mitomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 29 publications
(49 reference statements)
1
60
0
1
Order By: Relevance
“…The primary aim of this trial was to evaluate the toxicity of HIPEC with mitomycin C versus HIPEC with oxaliplatin. Progression‐free and overall survival did not differ between groups, but the overall results confirmed that long‐term survival is possible if complete cytoreduction is achieved 44 …”
Section: Principles Of Intraperitoneal Chemotherapymentioning
confidence: 53%
“…The primary aim of this trial was to evaluate the toxicity of HIPEC with mitomycin C versus HIPEC with oxaliplatin. Progression‐free and overall survival did not differ between groups, but the overall results confirmed that long‐term survival is possible if complete cytoreduction is achieved 44 …”
Section: Principles Of Intraperitoneal Chemotherapymentioning
confidence: 53%
“…32 A recent randomized controlled trial comparing Mitomycin C to Oxaliplatin did not show any significant advantage of one drug over the other on overall and disease free survival for appendiceal tumours. 33…”
Section: Hipecmentioning
confidence: 99%
“…The authors mentioned that no statistically significant differences were demonstrated in postoperative morbidity and that no randomized comparison of HIPEC with mitomycin (MMC) versus oxaliplatin has been performed. Actually, a recent multicentre, randomized trial evaluated haematologic toxicities as a result of HIPEC with oxaliplatin or mitomycin in patients with peritoneal metastases of appendiceal origin . The results of this trial demonstrated a significantly lower white blood cell count from postoperative days 5 to 10 in patients who received HIPEC with mitomycin.…”
mentioning
confidence: 99%